Skins and Sleeves for Soft Robotics: Inspiration from Nature and Architecture1. Issue 8 (15th January 2015) - Lekakou, Constantina; Elsayed, Yahya; Geng, Tao; Saaj, Chakravarthini M.
<x xml:space="preserve">Abstract</x> This paper is on the design, fabrication, and testing of skins and sleeves for soft robotics with the focus on the mechanical features of the microstructure of these skins, drawing inspiration from nature and architecture. Biological inspirations drawn from animals are used for designing skin membranes or skin structures for soft robotic actuators, in particular pneumatic actuators that protect, guide, and contribute to the development of the actuated shape. The results presented in this paper will be a new step toward advancing the state‐of‐the‐art of biologically inspired soft robots for minimally invasive surgery. Inspirations from architecture are of particular interest in the areas of formability of design and continuous flow. The report presents a trade‐off study using various skin and sleeve technologies of innovative fiber structures and combinations of different materials in different innovative designs, surrounding a pneumatically actuated, soft robot of variable stiffness.